De novo mutation in ELOVL1 causes ichthyosis, acanthosis nigricans, hypomyelination, spastic paraplegia, high frequency deafness and optic atrophy. Issue 3 (28th November 2018) - Mueller, Noomi; Sassa, Takayuki; Morales-Gonzalez, Susanne; Schneider, Joanna; Salchow, Daniel J; Seelow, Dominik; Knierim, Ellen; Stenzel, Werner; Kihara, Akio; Schuelke, Markus
Abstract : Background: Very long-chain fatty acids (VLCFAs) are essential for functioning of biological membranes. ELOVL fatty acid elongase 1 catalyses elongation of saturated and monounsaturated C22-C26-VLCFAs. We studied two patients with a dominant ELOVL1 mutation. Independently, Kutkowska-Kaźmierczak et al. had investigated the same patients and found the same mutation. We extended our study towards additional biochemical, functional, and therapeutic aspects. Methods: We did mutation screening by whole exome sequencing. RNA-sequencing was performed in patient and control fibroblasts. Ceramide and sphingomyelin levels were measured by LC-MS/MS. ELOVL1 activity was determined by a stable isotope-labelled [ 13 C]malonyl-CoA elongation assay. ELOVL1 expression patterns were investigated by immunofluorescence, in situ hybridisation and RT-qPCR. As treatment option, we investigated VLCFA loading of fibroblasts. Results: Both patients carried an identical heterozygous de novo ELOVL1 mutation (c.494C>T, NM_001256399; p.S165F) not deriving from a founder allele. Patients suffered from epidermal hyperproliferation and increased keratinisation (ichthyosis). Hypomyelination of the central white matter explained spastic paraplegia and central nystagmus, while optic atrophy was causative for reduction of peripheral vision and visual acuity. The mutation abrogated ELOVL1 enzymatic activity and reduced ≥C24 ceramides and sphingomyelins in patient cells. Fibroblast loading with C22:0-VLCFAs increased C24:0-ceramides and sphingomyelins. We found competitive inhibition for ceramide and sphingomyelin synthesis between saturated and monounsaturated VLCFAs. Transcriptome analysis revealed upregulation of modules involved in epidermal development and keratinisation, and downregulation of genes for neurodevelopment, myelination, and synaptogenesis. Many regulated genes carried consensus proliferator-activated receptor (PPAR)α and PPARγ binding motifs in their 5'-regions. Conclusion: A dominant ELOVL1 mutation causes a neuro-ichthyotic disorder possibly amenable to treatment with PPAR-modulating drugs.